Assessing Social Capital Indicators in Public Spaces in Central streets of the City of Sanandaj, Iran - Kyoumars Habibi; Nina Taoshih; Milad Pira (Journal of Regional and City Planning, 2022)
The social capital concept has been proposed alongside other capitals such as human capital, financial capital and economic capital. The aim of this research was to evaluate the social capital in streets, which are among the most dynamic urban public spaces. They provide physical connections for social interactions and consequently can enhance social capital. To this aim, four central crossroads of the city of Sanandaj, Iran were selected as a case study. This study is a descriptive analysis conducted by questioning 400 participants. The collected data were analyzed by using the SPSS (Statistical Package for the Social Sciences) software at the inferential and statistical levels. The findings showed that effective elements of streets to improve social capital include the promotion of environmental qualities and mixed land use related to social trust, the feeling of belonging, identity and place related to social norms, face-to-face relationships, and social participation related to social networks.